Determination of Tryptamines and β-Carbolines in Ayahuasca Beverage Consumed During Brazilian Religious Ceremonies. (22nd November 2019) - Santos, Mônica Cardoso; Navickiene, Sandro; Gaujac, Alain
Abstract: Ayahuasca is a potent hallucinogenic beverage prepared from Banisteriopsis caapi in combination with other psychoactive plants. N, N -dimethyltryptamine, tryptamine, harmine, harmaline, harmalol, and tetrahydroharmine were quantified in ayahuasca samples using a simple and low-cost method based on SPE and LC with UV diode-array detection. The experimental variables that affect the SPE method, such as type of solid phase and nature of solvent, were optimized. The method showed good linearity (r > 0.9902) and repeatability (RSD < 0.8%) for alkaloid compounds, with an LOD of 0.12 mg/L. The proposed method was used to analyze 20 samples from an ayahuasca cooking process from a religious group located in the municipality of Fortaleza, state of Ceará, Brazil. The results showed that concentrations of the target compounds ranged from 0.3 to 36.7 g/L for these samples.